2012
DOI: 10.1159/000345838
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Helicobacter pylori</i></b> Infection in Neuromyelitis Optica and Multiple Sclerosis

Abstract: Objective: To determine the Helicobacter pylori infection status in patients with multiple sclerosis (MS) and neuromyelitis optica (NMO) spectrum. Methods:H. pylori infection was certified by indirect immunofluorescence assay. Aquaporin-4 (AQP4) antibody was detected by cell-based assay. H. pylori seroprevalence was measured in 118 patients with NMO (n = 52), high-risk NMO (hrNMO, longitudinally extensive transverse myelitis, n = 17 and recurrent optic neuritis, n = 7), MS (n = 42) and healthy controls (n = 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 22 publications
4
41
1
1
Order By: Relevance
“…15 (Li et al, 2007, Mohebi et al, 2013, Pedrini et al, 2015, Kountouras et al, 2010, Long et al, 2013, Pezeshki et al, 2008. Our study failed to reveal any difference on the prevalence of anti-Hp antibodies between MS and HCs.…”
Section: Accepted Manuscriptcontrasting
confidence: 70%
See 1 more Smart Citation
“…15 (Li et al, 2007, Mohebi et al, 2013, Pedrini et al, 2015, Kountouras et al, 2010, Long et al, 2013, Pezeshki et al, 2008. Our study failed to reveal any difference on the prevalence of anti-Hp antibodies between MS and HCs.…”
Section: Accepted Manuscriptcontrasting
confidence: 70%
“…Reported data on the prevalence of anti-Hp antibodies in MS show considerable variation (Li et al, 2007, Long et al, 2013, Mohebi et al, 2013, Pedrini et al, 2015, Smyk et al, 2014, Wender, 2003. Thus, some authors found an increased frequency of anti-Hp antibodies in MS (Long et al, 2013), while others found a significantly lower prevalence of anti-Hp antibodies in MS compared to HCs…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Some studies have reported a significant negative correlation and suggested that H. pylori infection might exert a protective effect to reduce the risk of MS [15][16][17][18][19][20][21][22][23][24][25][26]. However, others have failed to determine any association between H. pylori infection and MS [27][28][29][30][31][32][33][34][35], and some studies reported a high prevalence of H. pylori infection in MS patients [36,37]. To obtain a more comprehensive estimate of the association we conducted a meta-analysis to determine the prevalence of H. pylori infection in patients with MS and healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, her myelitis occurrence maybe mainly associated with AQP4 antibodies autoimmunity. Although potential infections, such as helicobacter pylori [4,12], were associated with anti-AQP4 antibody positive status, no evidence has showed that syphilis infection was involved in the AQP4 autoimmunity. Therefore, neurosyphilis may be an asymptomatic and isolated episode in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed this autoantibody as an important contributor to TM pathology. Viral or bacterial infections [3,4] may be prodromal factors of TM, commonly stimulating an inappropriate immune attack in spinal cord. On the other hand, many infections can induce direct neuronal invasion, resulting in spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%